Comparative efficacy of combination immunotherapy and targeted therapy in the treatment of BRAF-mutant advanced melanoma: a matching-adjusted indirect comparison. (11th March 2019) - Atkins, Michael B; Tarhini, Ahmad; Rael, Michael; Gupte-Singh, Komal; O'Brien, Elliott; Ritchings, Corey; Rao, Sumati; McDermott, David F
Aim: Comparison of clinical outcomes of nivolumab + ipilimumab versus BRAF + MEK inhibitors (dabrafenib + trametinib or vemurafenib + cobimetinib) in BRAF -mutant advanced melanoma.Methods: Matching-adjusted indirect comparisons were conducted between nivolumab + ipilimumab (CheckMate 067/069 studies) and BRAF + MEK inhibitors (COMBI-d, COMBI-v and coBRIM studies). Overall survival (OS), progression-free survival and objective response rates were assessed.Results: After adjusting, nivolumab + ipilimumab showed improved OS versus dabrafenib + trametinib (hazard ratio [HR] = 0.64; 95% CI: 0.46–0.89) or vemurafenib + cobimetinib (HR = 0.56; 95% CI: 0.36–0.89); OS outcomes were similar at 1 year, with benefits emerging after 12 months; progression-free survival and objective response rates were similar. Grade 3/4 adverse events occurred in 54.1% with nivolumab + ipilimumab, 31.6% with dabrafenib + trametinib and 59.5% with vemurafenib + cobimetinib.Conclusion: Nivolumab + ipilimumab had significantly improved clinical outcomes versus BRAF + MEK inhibitors, with benefits increasing after longer follow-up. Ongoing randomized trials directly comparing these treatments are necessary to prospectively validate these findings.